Serum and Urine Galectin-3 as a Diabetic Nephropathy Predictive Biomarker - Saleh, Dalia M.; Rasheed , Manal K.; Hameed, Ali R. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Diabetic nephropathy (DN) is a major cause of end-stage kidney impairment in patients with type 2 diabetes mellitus (DM). Galectin-3 has been linked to the development of numerous pathological conditions. There is currently little information about the interaction between DN and galectin-3.Objectives: The use of serum and urine galectin-3 as a unique forecasting diagnostic in DN patients.Methods: The present study was conducted in Baquba Teaching Hospital, Specialized Consultation clinic, Internal Medicine Department, and Iraq Specialized Laboratory in Baquba, Diyala governorate between October 2021 and February 2022 on 150 individuals with type 2 diabetes. Individuals were divided into three groups: Fifty individuals with an albumin/creatinine ratio (ACR) of 30 mg/g (normoalbuminuria), 50 patients with an ACR of 30-300 mg/g (microalbuminuria), and 50 healthy individuals with an ACR of 30 mg/g (healthy control). All subjects were subjected to extensive clinical assessment and examination and laboratory investigations (HbA1c, serum creatinine, serum galectin-3 as well as ACR, which was calculated based on urine test).Results: The mean concentrations of serum and urine galectin-3 levels were noticeably greater in those with microalbuminuria than normoalbuminuria, (11.2±3.61), (7.0±2.17) as compared to (9.0± 1.32) (7.6± 1.72) respectively. Serum Galectin-3 showed a high sensitivity (100%) and specificity (86%). Urine Galectin-3 sensitivity was (98%) and specificity (78%).Conclusion: This study has shown that serum and urine galectin-3 are important predictors of DN development in people with type 2 diabetes.